2023
DOI: 10.1001/jamanetworkopen.2023.18904
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Bacteremia in Febrile Children and Young Adults With Sickle Cell Disease in a Multicenter Emergency Department Cohort

Abstract: ImportanceBacteremia is a major cause of morbidity and mortality in children and young adults with sickle cell disease (SCD), but among those presenting to the emergency department (ED) with fever, the absolute risk of, risk factors associated with, and outcomes of bacteremia are poorly defined.ObjectiveTo obtain contemporary data on the absolute risk of, risk factors associated with, and outcomes associated with bacteremia in children and young adults with SCD presenting to the ED with fever.Design, Setting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Sepsis in our population was rare (4%) and confirms the decreasing trend of severe infections in children with SCD thanks to prophylactic penicillin and vaccination [ 17 , 18 ]. In fact, in a recent multicenter retrospective cohort study that included patients with SCD younger than 22 years (young adults) presenting to emergency departments with fever found that bacteriemia was found only in 1.1% of patients (95% CI, 1.05-1.26%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis in our population was rare (4%) and confirms the decreasing trend of severe infections in children with SCD thanks to prophylactic penicillin and vaccination [ 17 , 18 ]. In fact, in a recent multicenter retrospective cohort study that included patients with SCD younger than 22 years (young adults) presenting to emergency departments with fever found that bacteriemia was found only in 1.1% of patients (95% CI, 1.05-1.26%) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Haemolysis, vaso-occlusion and vasopathies lead to acute chest crises, strokes and life-threatening bacterial infections, including meningitis, osteomyelitis and septic shock syndrome. 4 Because SCD families often belong to underprivileged populations, the management of such events is disrupting the fragile organisational structure and socioeconomical balance. 5,6 Blood transfusion and hydroxyurea are proven to avoid primary strokes.…”
mentioning
confidence: 99%